Evaluating the suitability of baobab fruit shells as substrate for growing oyster mushroom (Pleurotus ostreatus) - Tavarwisa, Delight Michael; Govera, Chido; Mutetwa, Moses; Ngezimana, Wonder (Hindawi, 2022)
The baobab fruit shells were evaluated for their suitability as a substrate for growing oyster mushrooms and compared to three base substrates (wheat straw, maize cobs, and sawdust) of 1 kg dry weight. The duration of developmental stages, mycelium vigor, yield, and biological efficiency of the oyster mushroom from the four different substrates were recorded. Yields from the first 3 harvests (flushes) were considered, as they were the most productive ones. Wheat straw demonstrated significantly (p<0.05) higher mycelial colonization rate taking an average of 23 days to complete full spawn run followed by baobab fruit shells, sawdust, and maize cobs which took averages of 25.8, 27.2, and 29.5 days, respectively. Baobab fruit shells had the longest number of days taken between full spawn run and first pinhead formation with an average of 14.4 days which was significantly different (p<0.05) to the wheat straw, sawdust, and maize cobs which had 7.4, 9.4, and 10.5 days. The highest yield was observed on the sawdust which had an average of 682 g followed by wheat straw with 594 g. Maize cobs and baobab fruit shells had the least yield of 518 g and 482 g, respectively. The results showed that baobab fruit shells could be used as a substrate for the cultivation of oyster mushrooms and it can be recommended for commercial cultivation of oyster mushrooms.